Roadmap to recovery: Reporting on a research taskforce supporting Indigenous responses to COVID‐19 in Australia. Issue 1 (22nd September 2020) - Moodie, Nikki; Ward, James; Dudgeon, Patricia; Adams, Karen; Altman, Jon; Casey, Dawn; Cripps, Kyllie; Davis, Megan; Derry, Kate; Eades, Sandra; Faulkner, Samantha; Hunt, Janet; et al.
Abstract: In April 2020 a Group of Eight Taskforce was convened, consisting of over 100 researchers, to provide independent, research‐based recommendations to the Commonwealth Government on a "Roadmap to Recovery" from COVID‐19. The report covered issues ranging from pandemic control and relaxation of social distancing measures, to well‐being and special considerations for vulnerable populations. Our work focused on the critical needs of Aboriginal and Torres Strait Islander communities; this paper presents an overview of our recommendations to the Roadmap report. In addressing the global challenges posed by pandemics for citizens around the world, Indigenous people are recognised as highly vulnerable. At the time of writing Australia's First Nations Peoples have been largely spared from COVID‐19 in comparison to other Indigenous populations globally. Our recommendations emphasise self‐determination and equitable needs‐based funding to support Indigenous communities to recover from COVID‐19, addressing persistent overcrowded housing, and a focus on workforce, especially for regional and remote communities. These latter two issues have been highlighted as major issues of risk for Indigenous communities in Australia It remains to be seen how governments across Australia take up these recommendations to support Indigenous peoples' health and healing journey through yet another, potentially catastrophic, health crisis.